2021
DOI: 10.1037/xlm0000984
|View full text |Cite
|
Sign up to set email alerts
|

On the segmentation of Chinese incremental words.

Abstract: In the present article, we report two eye-tracking experiments on how Chinese readers segment incremental words while reading Chinese. Incremental words are multicharacter words containing a subset of characters that constitute another word (referred to as the embedded word). For example, in a word containing three characters ABC (e.g., "老板娘," meaning landlady), the first two characters AB ("老板," meaning boss) constitute an embedded word. In the two experiments, Chinese readers read sentences with 3-character … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(34 citation statements)
references
References 27 publications
9
24
1
Order By: Relevance
“…Furthermore, J. Zhou and Li (2021) replicated the findings of Yang et al (2012) using a similar paradigm to investigate whether three-character compound words are integrated into sentence context as a whole.…”
Section: Chinese Word Identificationsupporting
confidence: 57%
See 1 more Smart Citation
“…Furthermore, J. Zhou and Li (2021) replicated the findings of Yang et al (2012) using a similar paradigm to investigate whether three-character compound words are integrated into sentence context as a whole.…”
Section: Chinese Word Identificationsupporting
confidence: 57%
“…Zhou and Li (2021) replicated the findings of Yang et al (2012) using a similar paradigm to investigate whether three-character compound words are integrated into sentence context as a whole. In J. Zhou and Li (2021), the first two characters of the three-character compound words constitute another word, and these two-character words were target words in the two-character word condition.…”
Section: Chinese Word Identificationmentioning
confidence: 99%
“…Finally, the word-superiority effect showed that character recognition is faster in real words than in nonwords (Chen et al, 2018). These studies suggest that words act as the basic processing units in Chinese reading (Zhou and Li, 2021;Li et al, 2022). When readers cannot simultaneously process all the characters belonging to a word, reading performance will be disturbed (Li et al, 2013).…”
Section: Introductionmentioning
confidence: 86%
“…Second, most set phrases are listed as words in Chinese dictionaries (Lexicon of Common Words in Contemporary Chinese Research Team, 2021, 7th edition). Finally, recent experimental studies have shown that idioms and set phrases in Chinese are processed as a whole, just as words (e.g., see Li & Ma, 2012; Li et al, 2009; Zang, 2019, Zang et al, 2021; Zhou & Li, 2021). For instance, Li et al (2009) asked Chinese readers to report as many characters as possible after they saw four briefly presented Chinese characters, participants could usually report all of the four characters when they belonged to a word, but they could only report the first two characters when the four characters belonged to two words.…”
mentioning
confidence: 99%